2021
DOI: 10.3389/fcvm.2021.715114
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Inflammation During Venous Remodeling of Arteriovenous Fistulae

Abstract: Vascular disorders frequently have differing clinical presentations among women and men. Sex differences exist in vascular access for hemodialysis; women have reduced rates of arteriovenous fistula (AVF) maturation as well as fistula utilization compared with men. Inflammation is increasingly implicated in both clinical studies and animal models as a potent mechanism driving AVF maturation, especially in vessel dilation and wall thickening, that allows venous remodeling to the fistula environment to support he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 117 publications
(145 reference statements)
0
13
0
Order By: Relevance
“…Up to 60% of AVF fail to mature by 5 months, preventing their use for hemodialysis. The failed AVF defined by updated NKF-KDOQI guidelines ( 92 ) may result from shear stress in new branch and bend of artery-connected vein, changes of blood flow direction and arterial blood pressure actin on vascular wall ( Figure 7A ), inflammation, and inappropriate venous inward and outward remodelings ( 20 ), contributing to stenosis, access failure, significant patient burden and healthcare cost ( 93 ). RNA-Seq data identified that in AVF, gene expressions associated with inflammation, TGF-β; and cell death pathways are significantly modulated ( 94 ).…”
Section: Resultsmentioning
confidence: 99%
“…Up to 60% of AVF fail to mature by 5 months, preventing their use for hemodialysis. The failed AVF defined by updated NKF-KDOQI guidelines ( 92 ) may result from shear stress in new branch and bend of artery-connected vein, changes of blood flow direction and arterial blood pressure actin on vascular wall ( Figure 7A ), inflammation, and inappropriate venous inward and outward remodelings ( 20 ), contributing to stenosis, access failure, significant patient burden and healthcare cost ( 93 ). RNA-Seq data identified that in AVF, gene expressions associated with inflammation, TGF-β; and cell death pathways are significantly modulated ( 94 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to limitations in imaging techniques, the biomolecular aspects of the formation of AVAs and how these structures could cause disease are still poorly understood, and are unexplored in the context of choroidal endothelium. Therefore, it would be of interest to explore the specific aspects of male and female human choroidal endothelium in the context of either AVAs or AVFs, and compare the endothelial features in AVAs or AVFs to other types of endothelium (Cai et al 2020;Kudze et al 2020;Chan et al 2021). This may also include studies to the effects of corticosteroids on endothelium, vascular smooth muscle cells or local autonomous nervous system activity as a pathological stimulus, as the biomolecular mechanisms underlying the associations between corticosteroids and CSC, and between corticosteroids and dural AVFs, are unknown (Nasr et al 2017;Brinks et al 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…After surgery, these shunts require a period of maturation, and these may fail for instance due to thrombosis. Of note, shunt maturation is much more likely to be successful in males compared with females (Miller et al 2003;Waheed et al 2020;Chan et al 2021;MacRae et al 2021). In a study that evaluated the outcomes of 230 surgically created shunts, the adequacy for dialysis was 31% in females compared with 51% in males (p = 0.001), despite routine preoperative mapping and interventions to rescue immature fistulas (Miller et al 2003).…”
Section: Corticosteroids and Sex Differences Are Associated With Both...mentioning
confidence: 99%
See 2 more Smart Citations